Drivers and approaches to the circular economy in manufacturing firms. (1st September 2019) - Gusmerotti, Natalia Marzia; Testa, Francesco; Corsini, Filippo; Pretner, Gaia; Iraldo, Fabio
Abstract: Much of the literature has investigated what the most innovative business models are in order to successfully implement circular economy principles within a company. However, the majority of modern companies are still based on traditional business models thus, it is important to study how to get these companies to adopt more circular practices. Data were collected through a questionnaire-based survey of 821 Italian companies. A cluster analysis was performed to classify their current level of implementation of the circular economy principles and a logit regression was carried out to identify the most effective drivers. Five clusters were identified: 1) "information-oriented companies" (24%), the best at communication and marketing-related activities, but the worst in relation to all the other aspects; 2) "linear companies" (41.6%), those that perform poorly in all five phases; 3) "green marketers" (15.5%), which perform well in relation to design, production and consumption; 4) "optimizers" (10.6%), which focus more on production and logistics and 5) "circular companies" (8.1%), those that register a good performance with respect to all aspects. The bad performers, clusters 1 and 2, also registered the worst economic results in the last three years, whereas the "circular champions" reported the best performance. Finally, the logit regression showed that economic drivers were the most effective at encouraging "linear companies" to adopt more circular business models. On the other hand, no significant evidence was found of any influence exerted by the drivers related to regulatory pressure, resource exploitation risks, and the pursuit of environmental values. Graphical abstract: Image 108 Highlights: There is still a low level of circularity in most Italian manufacturing companies. Economic drivers are the most important drivers of circular actions. Regulatory pressures, resource exploitation risks and environmental value drivers are still ineffective.